(untitled) (Jurnal Pendidikan Fisika, 2021)
This research aims to develop a valid, practical and effective basic physics practicum guide 2 used for students of the Physics Education Study Program of the Muslim University of Maros. This research employs a 4-D development model research with 4 stages, namely: Define Phase (Define), Planning Stage (Design), Development Stage (Develop), Dissemination Stage (Disseminate). The practicum guide was tested to 10 students of Physics Education in the even semester, the Academic Year of 2019/2020. The research instruments include validation sheets, observation sheets, and practicum assessment documentation. The results showed that the basic physics practicum guide 2 that was developed had met the valid criteria with a validity value of 0.93. Besides, the practices with the implementation of the device was mostly in category 3 and was found effective as 83% of the students reached scores above 70.